Perplexing findings during laparoscopic evaluation for tubal factor infertility resulting from a gastric leak after bariatric surgery: A case report - Alexandra M. Poch; Michael Dougherty; Robert A. Roman; Larisa Gavrilova-Jordan (Elsevier, 2022)
Tubal factor is the primary type of female infertility, accounting for 25-35% of cases. Common causes include inflammation due to pelvic inflammatory disease, septic abortion, tubal surgery, and surgical adhesions. Bariatric surgery is becoming increasingly popular as rates of obesity rise, with over 256,000 surgeries performed in 2019. Half of these procedures were performed on women of reproductive age. This is the first reported case of a patient with tubal factor infertility as a result of a gastric leak from a remote sleeve gastrectomy that led to extensive abdominal and pelvic adhesions.